MicroRNA‐181a restricts human γδ T cell differentiation by targeting Map3k2 and Notch2 - Gordino, Gisela (2021)
© 2021 The Authors. Published under the terms of the CC BY 4.0 license. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.